EFFECTS OF WEARING DIFFERENT MASKS ON CARDIOPULMONARY SYMPTOMS IN HEALTHY SUBJECTS (The Research of Medical Science Review, 2025)
Background: Mask has been used to protect body from many kinds of microorganisms include Bacteria, Viruses, fungus that spread from air to air or person to person. Masks has been used worldwide specially in recent corona virus out-break to reduce the morbidity and mortality rate. Its use to protect from harmful particles but also has effects on out cardio-pulmonary symptoms when used all the time. Aims and Objective: This Study was conducted to see the effect of masks on cardio- pulmonary symptoms during submaximal functional activity. Material and Methods: Total 30 participants were recruited with informed consents. Different masks used such as KN95, Surgical, Cloth and no mask on subjects with 4 rounds of 6MWT for 24-48 hours so that findings of leg fatigue score cannot be affected due to previous activity. Inclusion criteria was age between 18–25 years and both male and female. Exclusion Criteria was history of cardio-pulmonary disease, participants who were unable to perform pulmonary function, walking test and age < 18 and > 25. Results: Results shows that wearing different types of masks had no remarkable effect on systolic blood pressure, diastolic blood pressure, pulse rate and oxygen saturation as value of p was more than 0.05. In contrast, significant consequences of wearing different types of masks were observed on dyspnea and leg fatigue score with p value 0.000 which was less than 0.05. Conclusion: This study concludes that wearing different kind of masks while performing sub-maximal physical activity produces noticeable effects on respiratory symptoms mainly dyspnea and fatigue amid the healthy individuals